Lacticaseibacilli attenuated fecal dysbiosis and metabolome changes in Candida-administered bilateral nephrectomy mice - Chancharoenthana, Wiwat; Kamolratanakul, Supitcha; Visitchanakun, Peerapat; Sontidejkul, Supistha; Cheibchalard, Thanya; Somboonna, Naraporn; Settachaimongkon, Sarn; Leelahavanichkul, Asada (Frontiers in Immunology, 2023)
The impacts of metabolomic changes (reduced short-chain-fatty acids; SCFAs) in uremic condition is not fully understood. Once daily Candida gavage with or without probiotics (different times of administration) for 1 week prior to bilateral nephrectomy (Bil Nep) in 8-week-old C57BL6 mice as the possible models more resemble human conditions were performed. Candida-administered Bil Nep mice demonstrated more severe conditions than Bil Nep alone as indicated by mortality (n = 10/ group) and other 48 h parameters (n = 6-8/ group), including serum cytokines, leaky gut (FITC-dextran assay, endotoxemia, serum beta-glucan, and loss of Zona-occludens-1), and dysbiosis (increased Enterobacteriaceae with decreased diversity in microbiome analysis) (n = 3/ group for fecal microbiome) without the difference in uremia (serum creatinine). With nuclear magnetic resonance metabolome analysis (n = 3-5/ group), Bil Nep reduced fecal butyric (and propionic) acid and blood 3-hydroxy butyrate compared with sham and Candida-Bil Nep altered metabolomic patterns compared with Bil Nep alone. Then, Lacticaseibacillus rhamnosus dfa1 (SCFA-producing Lacticaseibacilli) (n = 8/ group) attenuated the model severity (mortality, leaky gut, serum cytokines, and increased fecal butyrate) of Bil Nep mice (n = 6/ group) (regardless of Candida). In enterocytes (Caco-2 cells), butyrate attenuated injury induced by indoxyl sulfate (a gut-derived uremic toxin) as indicated by transepithelial electrical resistance, supernatant IL-8, NFκB expression, and cell energy status (mitochondria and glycolysis activities by extracellular flux analysis). In conclusion, the reduced butyrate by uremia was not enhanced by Candida administration; however, the presence of Candida in the gut induced a leaky gut that was attenuated by SCFA-producing probiotics. Our data support the use of probiotics in uremia.